Estrategias metacognitivas en el progreso de la comprensión lectora en inglés en estudiantes de segundo grado de secundaria en la Institución Educativa Pública República de Venezuela 60050 de Iquitos 2022 - Escobedo Aguilar, Jairo Alex (2023)
This research was carried out to evaluate the impact of metacognitive strategies on the development of second year students’ reading comprehension in English at the República de Venezuela 60050 public school in Iquitos 2022. The type of research was evaluative, and field study, contemporary transectional, univariate and quasi-experimental designs with pre-test, post-test in the experimental group and the control. The investigation consisted of a population of 80 students, from which a non-probabilistic sample of 50 students was extracted, divided into two sets of 26 each. A valid and reliable reading comprehension test was used as a data collection tool. The product obtained, in the post test, shows that the mean score of the experimental group was higher than the control group (13.4 > 7.8). In the same way in its dimensions: getting information (15.0 > 11.2), inferencing and interpreting information (10.5> 3.3) and evaluation of text content, context and format (14.7 > 8.0). Therefore, the hypothesis of the present investigation was admitted, since the learner-training program based on metacognitive strategies generated a significant development on the students’ reading comprehension in English. (p-value = 0.000 < α = 0.05).